Polymorphic transposable elements contribute to variation in recombination landscapes - Yuheng Huang; Zita Y. Gao; Kayla Ly; Leila Lin; Jan-Paul Lambooij; Elizabeth G. King; Aniek Janssen; Kevin H.-C. Wei; Yuh Chwen G. Lee (Proceedings of the National Academy of Sciences, 2025)
Meiotic recombination is a prominent force shaping genome evolution, and understanding why recombination rates vary within and between species has remained a central, though challenging, question. Variation in recombination is widely thought to influence the efficacy of selection in purging transposable elements (TEs), prevalent selfish genetic elements, leading to widely observed negative correlations between TE abundance and recombination rates across taxa. However, accumulating evidence suggests that TEs could instead be the cause rather than the consequence of this relationship. To test this prediction, we formally investigated the influence of polymorphic, putatively active TEs on recombination rates. We developed and benchmarked an approach that uses PacBio long-read sequencing to efficiently, accurately, and cost-effectively identify crossovers (COs), a key recombination product, among large numbers of pooled recombinant individuals. By applying this approach to Drosophila strains with distinct TE insertion profiles, we found that polymorphic TEs, especially RNA-based TEs and TEs with local enrichment of repressive marks, reduce the occurrence of COs. Such an effect leads to different CO frequencies between homologous sequences with and without TEs, contributing to varying CO maps between individuals. The suppressive effect of TEs on CO is further supported by two orthogonal approaches–analyzing the distributions of COs in panels of recombinant inbred lines in relation to TE polymorphism and applying marker-assisted estimations of CO frequencies to isogenic strains with and without transgenically inserted TEs. Our investigations reveal how the constantly changing TE landscape can actively modify recombination, shaping genome evolution within and between species.